2023
DOI: 10.3390/app13052755
|View full text |Cite
|
Sign up to set email alerts
|

A Spatio-Temporal Analysis of Heat Island Intensity Influenced by the Substantial Urban Growth between 1990 and 2020: A Case Study of Al-Ahsa Oasis, Eastern Saudi Arabia

Abstract: Rapid urbanization has recently led to a significant propagation of heat islands. This study aimed to analyze the spatio-temporal variation in urban heat islands (UHIs) at Al-Ahsa Oasis in Saudi Arabia, in addition to exploring the urbanization influence on UHI distribution over the last 30 years. The spatial variability in UHIs was assessed, the key determinant elements were identified, and the forms of distribution were delineated. Change detection, hot spots, and spatial autocorrelation were employed to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…These increases took place upon barren lands and the oasis' vegetation cover (mainly date palm plantations). A substantial decrease in the vegetation cover and barren soil besides an increase in the urban area was detected between 1990 and 2020, because of the growth of the population all over the study site, which is possibly due to oil industry production as previously reported [19]. A reduction in vegetated cover by nearly 17% because of the rapid increase in urban development (more than 17% in 1990 to approximately 46% in 2020) was also reported in the same study.…”
Section: Yearssupporting
confidence: 85%
See 3 more Smart Citations
“…These increases took place upon barren lands and the oasis' vegetation cover (mainly date palm plantations). A substantial decrease in the vegetation cover and barren soil besides an increase in the urban area was detected between 1990 and 2020, because of the growth of the population all over the study site, which is possibly due to oil industry production as previously reported [19]. A reduction in vegetated cover by nearly 17% because of the rapid increase in urban development (more than 17% in 1990 to approximately 46% in 2020) was also reported in the same study.…”
Section: Yearssupporting
confidence: 85%
“…Moreover, the information given in Figure 10 shows that the population in the study area increased significantly during the period from 1990 to 2020, and according to Abdelatti et al [24], the population of the Al-Ahsa Oasis (see Figure 10) has apparently doubled since the oil discovery, and this increase in population might have contributed to the current urban growth as a main driving force. They concluded that the increase in urban areas might increase what is known as dark surfaces, and consequently, it may increase land surface temperatures and urban heat islands as documented recently by Hassablla and Salih [19].…”
Section: Driving Forces and Consequences Of Urban Fraction Changesmentioning
confidence: 86%
See 2 more Smart Citations